Unrecognised and unregistered visual impairment. Issue 10 (October 1994) - Robinson, R; Deutsch, J; Jones, H S; Youngson-Reilly, S; Hamlin, D M; Dhurjon, L; Fielder, A R
Abstract : Recent community based studies have shown that only a minority of visually impaired people who are eligible to be registered as partially sighted or blind are actually registered as such. To determine how many unregistered but eligible people are attending ophthalmic clinics a prospective study was undertaken of all patients (n = 1543) attending ophthalmic outpatient departments, at a single specialty eye hospital and two district general hospitals over a 1 week period. All patients with visual acuity < or = 6/18 or restricted visual field were interviewed. Registration status and factors affecting this were then determined. Although 95/174 patients interviewed were eligible for registration, 68 as partially sighted and 27 as blind, only 46 (48.4%) of these were registered. Asians and Afro-Caribbeans were under-represented in the group eligible for registration. Active treatment impeded registration. Patients having four or more hospital visits were on average 16 times more likely to be registered as those who had fewer attendances. Disabilities, in addition to visual impairment, were present in 40% (n = 38). This study shows that there is unregistered visual impairment in patients attending ophthalmic departments. As registration triggers multidisciplinary support, ophthalmologists need to be more alert to the benefits and criteria for partial sight and blind registration.